Understanding spatiotemporal symptom onset risk of Omicron BA.1, BA.2 and hamster-related Delta AY.127 - Tong, Chengzhuo; Shi, Wenzhong; Siu, Gilman Kit-Hang; Zhang, Anshu; Shi, Zhicheng (Frontiers in Public Health, 2022)
Purpose Investigation of the community-level symptomatic onset risk regarding severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern, is crucial to the pandemic control in the new normal. Methods Investigated in this study is the spatiotemporal symptom onset risk with Omicron BA.1, BA.2, and hamster-related Delta AY.127 by a joint analysis of community-based human mobility, virus genomes, and vaccinations in Hong Kong. Results The spatial spread of Omicron BA.2 was found to be 2.91 times and 2.56 times faster than that of Omicron BA.1 and Delta AY.127. Identified has been an early spatial invasion process in which spatiotemporal symptom onset risk was associated with intercommunity and cross-community human mobility of a dominant source location, especially regarding enhancement of the effects of the increased intrinsic transmissibility of Omicron BA.2. Further explored is the spread of Omicron BA.1, BA.2, and Delta AY.127 under different full and booster vaccination rate levels. An increase in full vaccination rates has primarily contributed to the reduction in areas within lower onset risk. An increase in the booster vaccination rate can promote a reduction in those areas within higher onset risk. Conclusions As the study has provided a comprehensive investigation about the spatiotemporal symptom onset risk of Omicron BA.1, BA.2, and hamster-related Delta AY.127, this study can assist countries and regions to prevent the emergence of these variants on a strategic basis. Moreover, this study provides scientifically derived findings on the impact of the full and booster vaccination campaigns on reducing the symptomatic infection.